(3JbQjQGJs - (3GdMSjfj, GdeQGZj, YHO GdaJGM Hf Ydjs ((3HNW GdeDdas)
(3ChdgG (B:s
(3CUd(B: (3GNJdahG aj Cf GdCeQ HGdTjA CUd gh CeQ HebOeGJg Ce dG(B...s
(3BNQgG (B:s
(3hGdehVhYGJ GdeSJfHWI haj GdehVhYGJ GdUQaI GdeJYdbI HYde GdQLGd Ydi eG GNJQfGg hJMbbfGg(B. (3gPG JeGe GdcJGHs
(3JHUQI GdYfhGf (B:s
(3JbQjQGJ aj GdCUhds
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs